The Identity Threat and Coping among the Followers of the Indigenous Javanese Religion - Muhammad Syafiq; Nadratul Zuniara Putri (Journal of Health and Behavioral Science, 2022)
The present study was aimed at exploring how the adherents of an indigenous Javanese religion, known as Javanism or Kejawen, maintain their identity in the hegemonic Muslim identity. This study employed a qualitative case study. The participants were the leader and key members of a Javanese religious group in Mojokerto District, East Java, Indonesia. Data were collected using semi-structured interviews and analyzed using thematic analysis. The study found that most participants experience threats to their identity. They are perceived as being targeted and stigmatized since they are practicing mythic rituals and believing in superstition. They reported that they are labeled as obsolete, outdated, and even idolatrous. To cope with the identity threats, participants employ both intrapsychic and interpersonal strategies. The results indicate that the followers of the indigenous Javanese religion can efficaciously maintain their positive identity in response to the negative stigma imposed by the surrounding Muslim people.